Sime Darbey Plantation Tower (SDPT) / Fatin Nur'ain Jafari ... [et al.] - Fatin Nur'ain, Jafari; Nurul Aqeesya, Abdul Aziz; Siti Nur 'Aqilah, Mohd Khairi; Mohammad Fikrul Hakim, Mohd Fadhillah; Nurul Izzati, Othman (2019)
Integrated Final Project contains ten chapters whereby each chapter will emphasize different aspect of studies in relation of Building Surveying.The contents of these chapters will revolve around the case study at Sime Darby Plantation Berhad. The building which is also known as the Plantation tower is a Gold Rated Green Building certified by LEEDS. The Integrated Facility Management with their main contractor,Stagno-Tech Sdn Bhd have been collaborating and working together to maintain the building status and condition. Their strategies will be further explain in this report. Multiple methods to gain information were implemented during this assignment. This includes interviews and several site visit to the case study. Furthermore, analysis of data collections are done with the help of consultations from the Sime Darby Plantation representative which is the building manager and our respective supervise.